Flow pattern in vortex diode: experiments and CFD simulations - Kulkarni, Amol A.; Ranade, V. V.; Rajeev, R.; Koganti, S. B. (AICHE Journal, 2008)
Vortex diodes are used as leaky nonreturn valves in applications, where it is desirable to avoid valves with moving parts. Despite their use in practice for several decades, no detailed analysis of the flow inside the vortex diodes is available. A strategy was derived for the CFD simulations of the vortical flow in diodes. A good agreement was seen between pressure drop (Delta P) across the inlet-outlet ports from CFD simulations, and the experimental data for five diode sizes. The simulations showed that in the reverse flow situation tangential velocity was dominant and resulted in conservation of angular momentum in the chamber until it reaches the axial exit port. This vortical motion induced a significant pressure drop (Delta P-r). The axial velocity gradient over the chamber cross-section helps in inducing relaminarization of the flow. In the forward flow mode, the fluid gets distributed radially over the chamber and exits through the tangential port, yielding low Delta P-f. The analysis showed that the performance of a diode is strongly affected by diode geometry, size, aspect ratio, nozzle configuration and Reynolds number. Among different configurations, the nozzles with entry port size equal to diode yielded higher diodicity. Simulations showed that using angle of divergence for diffuser sections of nozzles of the order of 7 degrees exhibited higher diodicity than smaller angles. It was also observed that at higher flow rates significantly higher diodicity was obtained using axial nozzles with larger radius of curvature for expander section. The modeling methodology and results presented will be useful for evolving better designs of vortex diodes.
Keywords: CFD; Diodicity; pressure drop; relaminarization; Vortex diode

Pressure equalization approach for flow uniformity in microreactor with parallel channels - Madane, Ketan; Kulkarni, Amol A. (Chemical Engineering Science, 2018)
Numbering-up using parallel channels helps to achieve higher processing capacity while retaining the advantages of microreactors. However it may also lead to non-uniformity in flow across all the channels. Here we report the CFD simulations and experimental observations on the extent of uniformity in the flow from an assembly of several parallel channels. In the conventional parallel channel geometry, smaller channel size (<300 m) as well as higher fluid viscosity is seen to give better flow uniformity. Inequality in pressure distribution at the inlet of a large number of parallel channels is overcome by having two `pressure equalization slots' at an equal distance from inlet and outlets that open in the respective manifolds. Having such an arrangement helped to reduce the standard deviation in the flow by almost 90% when compared to the conventional geometry. However the modification was seen to increase the extent of back mixing to some extent. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: CFD; Experiments; Flow distribution; microreactor; Numbering-up; Parallel channels

Antisolvent based precipitation: batch, capillary flow reactor and impinging jet reactor - Pal, Sayan; Madane, Ketan; Kulkarni, Amol A. (Chemical Engineering Journal, 2019)
A method for continuous antisolvent precipitation of ammonium perchlorate (AP) using a confined impinging jet reactor (CIJR) is studied. The geometry of the CIJR was optimized to achieve excellent mixing with a significant reduction in the particle deposition on walls. Initially, the experimental conditions were optimized in a batch system and then in a continuous capillary reactor. Later those conditions extended for antisolvent precipitation of AP in an impinging jet reactor using water and n-butyl alcohol as a solvent and antisolvent, respectively for optimum performance. The performance was compared with the experiments in batch mode as well as and in a continuous capillary reactor. Over a range of inlet jet velocity that corresponded to 1792 < Re < 7193 for the saturated aqueous solution of AP and 1135 < Re < 4553 for the antisolvent butanol phase, 8.98-16.98 mu m Ammonium perchlorate particles were attained.
Keywords: Ammonium perchlorate; Antisolvent precipitation; CFD; continuous flow; Impinging jet reactor; microparticles